Ferdowsi, the Mongols and the history of Iran : art, literature and culture from early Islam to Qajar Persia : studies in honour of Charles Melville /: art, literature and culture from early Islam to Qajar Persia : studies in honour of Charles Melville. (2013) - Unknown
No abstract available